Reflections on a Legacy: Thoughts from Scholars about Agenda-Setting Past and Future. Issue 4 (4th July 2022) - Schmierbach, Mike; McCombs, Maxwell; Valenzuela, Sebastián; Dearing, James W.; Guo, Lei; Iyengar, Shanto; Kiousis, Spiro; Kosicki, Gerald M.; Meraz, Sharon; Scheufele, Dietram A.; Stoycheff, Elizabeth; Vargo, Chris; et al.
ABSTRACT: In response to Perloff's (this issue) essay examining the development and future of agenda setting, a series of scholars offer their own reactions to the essay and the broader issues it raises.